'A Local Terrorist Made Good': the Callaghan government and the Arab–Israeli peace process, 1977–79. Issue 1 (2nd January 2017) - Ashton, Nigel
Abstract: The British government had played an important role during the 1950s and 1960s as a mediator in the Arab–Israeli conflict, most notably through the development of Project Alpha between 1954 and 1956, and through the negotiation of United Nations Security Council resolution 242 in 1967. Between 1977 and 1979, British Prime Minister James Callaghan played a supporting role to US President Jimmy Carter as he negotiated the Camp David Accords of 1978. Callaghan adopted a pro-Israeli stance, cultivating close relations with the Israeli Prime Minister Menachem Begin and defending Begin's position over key issues, particularly his reluctance to remove settlements from the occupied territories. In this respect Callaghan's government departed from established British policy, even abstaining over United Nations Security Council resolution 446 in March 1979 which condemned continuing Israeli settlement activity. This resulted in damage to Britain's relations with moderate Arab states such as Egypt and Jordan.